(untitled) (San Francisco, 2001)
ASP, ADO, and XML Complete is a one-of-a-kind computer book-valuable both for its extensive content and its low price. This book contains a wealth of vital information for any developer in need of a complete reference to the most essential technologies used for Web programming on the Windows platform.
Keywords: Active server pages,ADO (Computer program),XML (Document markup language),Web sites,Web servers,Internet programming; Authoring programs